Return of the lysergamides. Part VI: Analytical and behavioural characterization of 1‐cyclopropanoyl‐d‐lysergic acid diethylamide (1CP‐LSD). Issue 6 (20th April 2020) - Brandt, Simon D.; Kavanagh, Pierce V.; Westphal, Folker; Stratford, Alexander; Odland, Anna U.; Klein, Adam K.; Dowling, Geraldine; Dempster, Nicola M.; Wallach, Jason; Passie, Torsten; Halberstadt, Adam L.
Abstract: Lysergic acid diethylamide (LSD) is a prototypical serotonergic psychedelic drug and the subject of many clinical investigations. In recent years, a range of lysergamides has emerged with the production of some being inspired by the existing scientific literature. Others, for example various 1‐acyl substituted lysergamides, did not exist before their appearance as research chemicals. 1‐Cylopropanoyl‐LSD (1CP‐LSD) has recently emerged as a new addition to the group of lysergamide‐based designer drugs and is believed to be psychoactive in humans. In this investigation, 1CP‐LSD was subjected to detailed analytical characterizations including various mass spectrometry (MS) platforms, gas and liquid chromatography, nuclear magnetic resonance spectroscopy, solid phase and GC condensed phase infrared spectroscopy. Analysis by GC–MS also revealed the detection of artificially induced degradation products. Incubation of 1CP‐LSD with human serum led to the formation of LSD, indicating that it may act as a prodrug for LSD in vivo, similar to other 1‐acyl substituted lysergamides. The analysis of blotters and pellets is also included. 1CP‐LSD also induces the head‐twitch response (HTR) in C57BL/6 J mice, indicating that it produces an LSD‐like behavioural profile. 1CP‐LSD induced the HTR with an ED50 = 430.0 nmol/kg which was comparable to 1P‐LSD (ED50 = 349.6 nmol/kg) investigated previously. Clinical studies are required to determine the potency and profile of the effects produced by 1CP‐LSD in humans. Abstract : 1‐Cylopropanoyl‐ d ‐lysergic acid diethylamide (1CP‐LSD), a recently emerged designer drug, was subjected to analytical characterizations combined with the assessment of behavioural effects in C57BL/6J mice using the head‐twitch response (HTR). 1CP‐LSD induced the HTR with an ED50 = 430.0 nmol/kg which suggests that it might display LSD‐like effects in humans.